Egypt’s Youth Outside Work and Education - Dietrich, Tabea (World Bank, Washington, DC, 2017)
This knowledge notes based on Egypt’s Youth who are not in Education, Employment or Training (NEET) are studied in this note, presenting the first in-depth analysis of Egypt's NEET youth, including demographic profiles and risk factors. The three main risk factors associated with an increased probability of NEET are (i) low education, (ii) living in remote areas and (iii) gender. Based on these findings, conclusions and recommendations are developed to help target the NEETs phenomenon in Egypt.